2005
DOI: 10.1152/ajpcell.00034.2005
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of new Staphylococcus aureus-RBC adhesion mechanism independent of fibrinogen and IgG under hydrodynamic shear conditions

Abstract: Ϫ1 and decreasing adhesion with increasing shear. The heteroaggregates formed after shear are stable when subjected to the shear rate 2,000 s Ϫ1 , indicating that intercellular contact time rather than shear forces controls the adhesion at high shear. S. aureus binding to RBC requires plasma, and 10% plasma is sufficient for maximal adhesion. Plasma proteins involved in the cell-cell adhesion, such as fibrinogen, fibronectin, von Willebrand factor, IgG, thrombospondin, laminin, and vitronectin are not involved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…Although S. aureus strains depending on external thiamine supply have been observed [35], there are no reports of thiamine uptake capabilities to date, which would – in additional to de novo synthesis - feed the intracellular thiamine pool in S. aureus . Interestingly, S. aureus is known to be adhesive to erythrocytes - a source of thiamine [36], [37] - which might emphasise uptake of this nutrient from red blood cells.…”
Section: Resultsmentioning
confidence: 99%
“…Although S. aureus strains depending on external thiamine supply have been observed [35], there are no reports of thiamine uptake capabilities to date, which would – in additional to de novo synthesis - feed the intracellular thiamine pool in S. aureus . Interestingly, S. aureus is known to be adhesive to erythrocytes - a source of thiamine [36], [37] - which might emphasise uptake of this nutrient from red blood cells.…”
Section: Resultsmentioning
confidence: 99%
“…As for the majority of in vitro experiments, the transferability of our results is challenged by issues that need to be addressed in further studies. The experiments were performed using isolated PMNs instead of whole blood which artificially excludes disruptive factors, such as S. aureus binding to erythrocytes and platelets [48, 49]. The chosen assay medium can influence the functionality and viability of PMNs; however our choice, KRb, is supported by a recent publication by Alhede et al [50].…”
Section: Discussionmentioning
confidence: 99%
“…The head domain, once assembled, then adheres to the host ECM via, for example, collagen, vitronectin or fibronectin [ 58 ]. Recent work showed that different adhesins bind differently to ECM components and that binding is dramatically influenced by shear forces [ 56 , 61 , 62 , 63 ]. In general, improving our understanding of adhesin–receptor interaction requires more detailed insights into their structural aspects [ 64 ].…”
Section: Microbial Adhesin–receptor Pairsmentioning
confidence: 99%